Changing Epidemiology of Acute Respiratory Infections in Under-Two Children in Dhaka, Bangladesh - Vidal, Karine; Sultana, Shamima; Patron, Alberto Prieto; Salvi, Irene; Shevlyakova, Maya; Foata, Francis; Rahman, Mahbubur; Deeba, Iztiba Mallik; Brüssow, Harald; Ahmed, Tahmeed; Sakwinska, Olga; Sarker, Shafiqul Alam (Frontiers in Pediatrics, 2022)
Objectives: Risk factors for acute respiratory infections (ARIs) in community settings are not fully understood, especially in low-income countries. We examined the incidence and risk factors associated with ARIs in under-two children from the Microbiota and Health study. Methods: Children from a peri-urban area of Dhaka (Bangladesh) were followed from birth to two years of age by both active surveillance of ARIs and regular scheduled visits. Nasopharyngeal samples were collected during scheduled visits for detection of bacterial facultative respiratory pathogens. Information on socioeconomic, environmental and household conditions, and mother and child characteristics were collected. A hierarchical modeling approach was used to identify proximate determinants of ARIs. Results: Of 267 infants, 87.3% experienced at least one ARI episode during first two years of life. The peak incidence of ARIs was 330 infections per 100 infant-years and occurred between two and four months of age. Season was the main risk factor (rainy monsoon season, Incidence Rate Ratio [IRR] 2.43 [1.92 - 3.07]; cool dry winter, IRR 2.10 [1.65 - 2.67] compared to hot dry summer) in the first two years of life. In addition, during the first six months of life, young maternal age (<22 years; IRR 1.34 [1.01 – 1.77]) and low birth weight (< 2500 g; IRR: 1.39 [1.03 – 1.89]) were associated with higher ARI incidence. Conclusions: Reminiscent of industrialized settings, cool rainy season rather than socioeconomic and hygiene conditions was a major risk factor for ARIs in peri-urban Bangladesh. Understanding the causal links between seasonally variable factors such as temperature, humidity, crowding, diet and ARIs, will inform prevention measures.